Analysis of Socio-cultural Contexts in the Transition from Traditional to Modern Literary Criticism in Kurdish Literature in the Mid and Late Twentieth Century - Shiler Rahmani (پژوهشنامه ادبیات کردی, 2022)
Literary criticism in today's sense is a new branch of knowledge. From its sparks to reaching the stage of perfection and prosperity and theoretical criticism, it has traveled a long way, and various factors were involved in it. Literary criticism has gone through stages from its beginnings, which was mostly poetry criticism and praise, to reaching the point of prosperity, and many side factors have played a role in this direction. Factors such as the role of magazines and newspapers, publishing houses and printing houses, the renewal of poetry flow, the development of academic discourse and the expansion of scientific associations, poet critics and literary movements each played a role in drawing the general image of criticism. This article has identified the role of each of the influential factors in Kurdish literary criticism by researching all kinds of literary works. As the consequence of the influence of these factors, the way for new discussions and critiques and theoretical foundations to literary criticism in Kurdish literature was opened. This article explores the most important cultural and social factors of the emergence of modern literary criticism in Central Kurdish language in the middle and the end of the twentieth century.